The quantum conductance of ballistic microconstrictions in metals with an open Fermi surface - Namiranian, A.; Kolesnichenko, A. (Физика низких температур, 2000)
It is shown that the conductance G of a quantum microconstriction in a metal with an open Fermi surface undergoes jumps e²/h of the opposite sign as a function of the contact diameter. The negative jumps are a result of the limitation of the energy of the electron motion along the direction in which the Fermi surface is open. The point contact spectrum dG/dV of such a constriction has additional peaks at the bias eV where the maximum energy εmaxεmax of the quantum subband is equal to the energies εF±eV/2 (εF is the Fermi energy).